Admission Serum Procalcitonin Thresholds and the PELOD-2 Score: A Prospective Analytical Study for Identifying Risk Ratios of Severe Organ Dysfunction in Pediatric Critical Care - Raisa Amini; Pudjiastuti; Sri Lilijanti (HM Publisher, 2026)
Background: Multiple organ dysfunction syndrome (MODS) remains a predominant cause of mortality in Pediatric Intensive Care Units (PICUs). While the Pediatric Logistic Organ Dysfunction-2 (PELOD-2) score is the established standard for assessing severity, it requires time-consuming serial calculations. There is an urgent need for a rapid, admission-based prognostic biomarker. This study evaluates the association between serum procalcitonin (PCT) and the severity of organ dysfunction in critically ill children. Methods: A prospective cross-sectional study was conducted at Dr. Moewardi Regional General Hospital, Indonesia, involving 25 children aged 1 month to 18 years with suspected infection. Organ dysfunction was quantified using the PELOD-2 score, and serum PCT was measured via Enzyme-Linked Fluorescent Assay (ELFA) within 24 hours of admission. Statistical analysis utilized Spearman’s rank correlation, multivariate linear regression, and Receiver Operating Characteristic (ROC) curve analysis. Results: The cohort had a median age of 12 months. The median PCT level was 0.88 ng/mL. A significant positive correlation was observed between serum PCT and PELOD-2 scores (r = 0.39, p = 0.051; multivariate beta = 0.42, p = 0.043). ROC analysis identified a PCT threshold of greater than 11 ng/mL as the optimal indicator for moderate-to-severe organ dysfunction (AUC 0.82). Patients exceeding this threshold had a significantly elevated risk (Risk Ratio = 2.20; 95 percent CI: 1.15–4.24; p = 0.035). Conclusion: Early serum procalcitonin measurement serves as a powerful independent factor associated with organ dysfunction severity. A cutoff value of greater than 11 ng/mL significantly stratifies risk, allowing clinicians to anticipate the progression of organ failure.